Pengaruh Intellectual Capital Terhadap Kualitas Laba Pada bank Umum Syariah di Indonesia - Fazira, Fira; Nurbaiti, Nurbaiti; Harahap, Muhammad Ikhsan (Journal of Student Development Informatics Management (JoSDIM), 2024)
This study is to determine the effect of Intellectul Capital instruments on the quality of profit in Islamic commercial banks in Indonesia. Intellectuul Capital is calculated using Value Added Intellectual Capital (VAIC) method from Pulic with Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and Structural Capital Value Added (STVA). This study uses a quantitative approach with secondary data sources derived from the annual financial statements of each bank. Data types using data panel with IBM SPSS 25 data processing software. The sample in this study as many as eight Islamic commercial banks in Indonesia, namely PT. Bank Aceh Syariah, PT. Bank Muamalat Indonesia, Tbk., PT. Bank Jabar Banten Syariah, PT. Bank Panin Dubai Syariah, Tbk., PT. Bank Syariah Bukopin, PT. BCA Syariah, PT. Bank Tabungan Pensiunan Nasional Syariah and PT. Bank Aladin Syariah during the period 2017-2021. This study uses multiple linear regression analysis. The results of this study stated that VACA variable has a significant effect on the quality of profit by 1.8%, vahu variable has a significant effect on the quality of profit by 2.8% and stva variable has no significant effect on the quality of profit by 21.3%. Simultaneously Vaca, VAHU and STVA variables significantly affect the quality of profit in Islamic commercial banks in Indonesia.